Conflict, Language, and Social Practice in Medieval Societies - Escalona, Julio; Castro, Álvaro Carvajal; Pérez-Alfaro, Cristina Jular (Brepols, 2024)
Isabel Alfonso is one of the finest scholars on the rural and political history of the European Middle Ages. She is widely known for her contributions to the study of the peasantry, social conflict, and political discourses. Her research has transcended the boundaries of medieval studies, incorporating insights from disciplines beyond including legal anthropology, philology, and discourse analysis, among others. Over her academic career Isabel Alfonso has made a continued effort to make the work of international scholars known in Spain and to communicate advancements in Spanish historiography to international audiences; and yet most of her own research has only been published in Spanish. As a means to acknowledge her long-standing commitment to bridge different historiographies and overcome national boundaries, this unusual <span class=